Error compensation of complex three-dimensional surfaces machined on computer-numeric-control grinding machine tools - Raoufinia, M.; Petrakov, Y.; Ataei, A.; Parand, Reza; Abou-El-Hossein, K. (2009)
This study discusses the development of a method for compensating profile errors, resulting from the deviation of the actual grinding wheel radius from the calculated one. The study also elaborates on a control strategy that may be followed to minimise the profile error and allow the use of a four-axis grinding machine instead of five-axis one to perform the same machining task. This approach can be completely justified when the reduction in the machining cost is achieved as a result of grinding the gauge profile on a four-axis CNC machine tool instead of the five-axis one. When a number of five segments are chosen, the first control program is established for the first mean radius (170 mm) of the first segment. When the grinding wheel radius reaches 150 mm as a result of wheel dressing, a new control program that will consider a new nominal radius of 160 mm will be activated. © 2009 Asian Network for Scientific Information.